2013
DOI: 10.1021/jp4028468
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Comparison of the Dealumination in SSZ-13 and the Desilication in SAPO-34

Abstract: With the purpose of understanding the behavior of aluminosilicate zeolites and silicoaluminophosphates (SAPOs) in the presence of steam, we carried out a computational density functional theory (DFT) study on the desilication of SAPO-34. The mechanism studied was a stepwise hydrolysis of the four bonds to the Si heteroatom. An analogous process to the desilication of SAPO-34 is the dealumination of SSZ-13. To investigate possible mechanistic differences between the two processes, we compared the results of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 26 publications
(34 reference statements)
4
62
2
Order By: Relevance
“…Recently, Aramburo et al [25] reported no difference with the purely thermally treated samples [31,34,35], i.e., a reduction in acidity with migration of silicon species to silicon islands. However, in an earlier contribution Park et al [37] showed that SAPO-34 thermally treated at 750ºC loses more crystallinity after reaction Theoretical calculations on the role of steaming on clusters of isomorphous zeolite SSZ-13 and SAPO-34 [38] also to support our hypothesis on the effect of steaming on SAPO-34 stability.…”
Section: The 29supporting
confidence: 82%
See 1 more Smart Citation
“…Recently, Aramburo et al [25] reported no difference with the purely thermally treated samples [31,34,35], i.e., a reduction in acidity with migration of silicon species to silicon islands. However, in an earlier contribution Park et al [37] showed that SAPO-34 thermally treated at 750ºC loses more crystallinity after reaction Theoretical calculations on the role of steaming on clusters of isomorphous zeolite SSZ-13 and SAPO-34 [38] also to support our hypothesis on the effect of steaming on SAPO-34 stability.…”
Section: The 29supporting
confidence: 82%
“…In this case, steaming at temperatures of 750ºC or higher and high partial pressures of water are used for simulating an equilibrium catalyst. However, this kind of hydrothermal stability test does not seem suitable for SAPO-34 since the mechanism of dealumination for zeolites is different from the desilication on silicoaluminophosphates [38]. In fact, while steaming at high temperature generates wide dealumination in ZSM-5 crystals with severe loss of acidity [47][48][49], in the case of standard SAPO-34, both, textural and acidity properties are preserved (see Table 1 and ref.…”
Section: Influence Of Stabilization On Catalyst Selectivitymentioning
confidence: 99%
“…The protons are connected to Al atoms as part of a ligand. The different locations of the protons may lead to possible mechanistic differences in hydrothermal aging [33]. Indeed, it was reported that the crystal structure of SAPO-34 can be maintained up to 1000-1200 • C even in the presence of moisture [34].…”
Section: Different Hydrothermal Stabilities Of Cu-ssz-13 and Cu-sapo-34mentioning
confidence: 99%
“…This rapid loss of structural integrity and acidity has become a major drawback for the practical application of SAPO-34. Several research groups have investigated this deactivation phenomenon and proposed potential deactivation mechanisms, such as Si-O-Al bonds opening [3][4][5] and P-O-Al bonds opening [6,7]. In addition, Janssen et al [8] proposed methods to inhibit the skeleton collapse of SAPO molecular sieve by using templates and carbonaceous material to shield the catalytic sites from contacting with H 2 O molecules.…”
Section: Introductionmentioning
confidence: 99%